PENERAPAN SISTEM REKAM MEDIS PASIEN BERBASIS WEBSITE DI PUSKESMAS KELURAHAN SIDODADI - Yunita Afril Tisa; Herman Saputra; Nasrun Marpaung (J-Com (Journal of Computer), 2023)
Abstract: Puskesmas as a public health technical service unit (UPT) facilitated by the government. Medical record data at the Sidodadi Health Center is processed manually and has a weakness, which requires a long time to find medical record data, because the data is still in the form of print media. The purpose of this study can be to build and design applications that can find out the process of managing patient medical records, to design a medical record information system equipped with facilities to facilitate admins in inputting patient data. This research method is carried out with a qualitative descriptive method approach while the method in system development uses a waterfall model. Based on the results of the following study, the application of this medical record system to conduct examinations on patients based on websites so that it is easier and more accurate. It can be concluded that the medical record system applied based on the Website can manage medical record data faster because the management process is no longer handwritten which results in very long queues so many patients have to wait for medical record examinationsKeywords : e-application; puskesmas; information system. Abstrak: Puskesmas menjadi layanan kesehatan masyarakat yang difasilitasi oleh pemerintah. permasalahan yang terjadi pada Puskesmas Sidodadi dalam pengolahan ata rekam medis yang dilakukan dengan cara manual, karena data masih berbentuk media cetak. Tujuan penelitian ini dapat membangun dan merancang aplikasi yang dapat mengetahui proses pengelolaan rekam medis pasien, untuk merancang sistem informasi rekam medis yang dilengkapi dengan fasilitas untuk memudahkan admin dalam menginputkan data-data pasien. Metode penelitian ini dilakukan dengan pendekatan metode deskriptif kualitatif sedangkan metode dalam pengembangan sistem menggunakan model waterfall. Berdasarkan hasil penelitian berikut penerapan system rekam medis ini untuk melakukan pemeriksaan pada pasien berbasis website sehingga lebih mudah dan akurat. Dapat disimpulkan system rekam medis yang diterapkan berbasis Website dapat mengelola data rekam medis lebih cepat karena  pada proses pengelolaannya tidak lagi ditulis tangan yang mengakibatkan antrian sangat panjang sehingga banyak pasien harus menunggu dalam pemeriksaan rekam medis.Kata kunci : e-aplikasi; puskesmas; sistem informasi.